Enantioselective total synthesis of cis-(+)- and trans-(+)-disparlure. Issue 34 (23rd August 2017) - Garg, Yuvraj; Kumar Tiwari, Anand; Kumar Pandey, Satyendra
Graphical abstract: Highlights: cis -(+)-Disparlure, a female gypsy moths sex pheromone. A concise and efficient asymmetric general approach for disparlure. Organocatalytic MacMillan's self aldol reaction and Wittig olefination key steps. Regioselective ring opening of an epoxide and Mitsunobu esterification reactions. Abstract: An expedient enantioselective synthetic approach for the gypsy moth sex-attractant pheromone cis -(+)-1 and trans -(+)-disparlure2 is described employing the optimized combination of organocatalytic MacMillan's self aldol reaction, Wittig olefination, regioselective ring opening of an epoxide and Mitsunobu esterification reactions as key steps.